Application‐Targeted Metal Grid‐Enhanced Transparent Electrodes for Organic Photovoltaics - Nick Burridge (Advanced Electronic Materials, 2025)
Transparent conducting electrodes (TCEs) are integral components in optoelectronic devices, facilitating both light transmission and electrical conduction. Over the past four decades, substantial advancements have been made in TCE materials, including transparent conducting oxides (TCOs) such as indium tin oxide (ITO) and fluorine-doped tin oxide (FTO), which remain dominant technologies in practical applications. Despite these advancements, current TCEs exhibit relatively high sheet resistance (Rsheet), posing a significant barrier to the scale-up of solution-processed devices such as organic photovoltaics (OPVs). This work addresses the scaling limitations of TCEs in OPVs by proposing the integration of a TCE with a metallic grid (g-TCE) to mitigate the high Rsheet issue. The performance of g-TCEs in OPVs is evaluated across various irradiance levels and TCE Rsheet values. Additionally, a novel, unitless figure-of-merit tailored to specific PV devices is introduced, which enables benchmarking beyond traditional TCE FoMs. Exemplifications of g-TCEs include aluminium-doped zinc oxide (AZO), which has an equivalent Rsheet of 0.5 Ω □−1, while maintaining an average visible transmittance exceeding 77%, outperforming all state-of-the-art monolithic TCE materials. These findings demonstrate that g-TCEs present a viable pathway for the development of large-area, solution-processed PV devices.